Wavelet Transform Application for Biomedical Data Mining – A Review - T.Selvapriya, Dr.V.R.Kavitha (International Journal of Advanced Science and Technology, 2020)
Data mining plays a vital role in several biomedical applications. In medical systems several data in the form of text, image,  signal and video are present. These data are to be mined to understand the normal or abnormal activities of several organs. In past manual methods were used by the physician to investigate the disease, but nowadays autonomous methods in data mining does the work in an efficient way. For analysis the information has to be extracted. Several methods like time, frequency and time scale analysis were present. Among them the Wavelet transform is efficient. The paper presents the detail investigation of the wavelet transform in Data Mining for investigation biomedical data is considered. The analysis has widened in De noising, extraction of features and classification. From the review its been found that the wavelet transform plays a vital role in Data mining of Biomedical data. The wavelet method for De noising, Extraction, Classification were analyzed.